Between Disability and Illness in Ancient Rome - The Case of Emperor - Myongjoo SHIN (Uisahak)
Claudius, the fourth emperor of Rome, suffered from multiple health issues, including an unsteady gait, persistent tremors in his arms and head, and a speech impediment that caused him to stutter and mispronounce words since childhood. Despite possessing average or even above-average intellectual abilities, he was considered unfit for public office (cursus honorum) due to these physical conditions.Based on remaining historical records, modern scholars have proposed several possible diagnoses, including cerebral palsy, dystonia, transverse myelitis, or Tourette syndrome. While earlier scholarship argued that he had cerebral palsy, more recent interpretations favor dystonia or Tourette syndrome. This claim is supported by historical records that show how Claudius' symptoms fluctuated over time since his childhood and how he was able to maintain a relatively stable health during his reign, carrying out his imperial duties effectively.Claudius’s physical impairments subjected him to harsh treatment from his family. His mother Antonia the Younger, his sister Livilla, and his paternal grandmother Livia treated him with contempt. In contrast, his adoptive grandfather Augustus showed some leniency, expressing hope that Claudius’ condition might improve one day. None the less, both Augustus and his uncle Tiberius chose to excluded him from public service. His disabilities, especially his walking and speech issues, remained a source of ridicule even after his death. This is poignantly illustrated in Seneca’s satirical poem “Apocolocyntosis,” which was written after his death.Unable to become a celebrated soldier or orator due to his physical limitations, Claudius was far removed from the Roman ideal of leadership both in his own times and in posterior times. He was often met with contempt and discrimination. Nevertheless, he proved to be a capable and successful emperor. Although none of his contemporary historians explicitly recorded the efforts Claudius may have made to overcome his disabilities, such perseverance can be inferred from the subtext of historical accounts. In this, Claudius offers a powerful symbol of resilience and hope.